Effect of Electrostatic Field Strength on Bioelectrochemical Nitrogen Removal from Nitrogen-Rich Wastewater - Anna Joicy; Young-Chae Song; Jun Li; Sang-Eun Oh; Seong-Ho Jang; Yongtae Ahn (Energies, 2020)
The effect of electrostatic fields on the bioelectrochemical removal of ammonium and nitrite from nitrogen-rich wastewater was investigated at strengths ranging from 0.2 to 0.67 V/cm in bioelectrochemical anaerobic batch reactors. The electrostatic field enriched the bulk solution with electroactive bacteria, including ammonium oxidizing exoelectrogens (AOE) and denitritating electrotrophs (DNE). The electroactive bacteria removed ammonium and nitrite simultaneously with alkalinity consumption through biological direct interspecies electron transfer (DIET) in the bulk solution. However, the total nitrogen (ammonium and nitrite) removal rate increased from 106.1 to 166.3 mg N/g volatile suspended solids (VSS).d as the electrostatic field strength increased from 0.2 to 0.67 V/cm. In the cyclic voltammogram, the redox peaks corresponding to the activities of AOE and DNE increased as the strength of the electrostatic field increased. Based on the microbial taxonomic profiling, the dominant genera involved in the bioelectrochemical nitrogen removal were identified as Pseudomonas, Petrimonas, DQ677001_g, Thiopseudomonas, Lentimicrobium, and Porphyromonadaceae_uc. This suggests that the electrostatic field of 0.67 V/cm significantly improves the bioelectrochemical nitrogen removal by enriching the bulk solution with AOE and DNE and promoting the biological DIET between them.